Semi-Active Control of Seismic Response on Prestressed Concrete Continuous Girder Bridges with Corrugated Steel Webs - Shangmin Zheng; Qiang Shen; Chong Guan; Haigen Cheng; Haiyan Zhuang; Man Zhou (Applied Sciences, 2022)
To improve the seismic capacity of prestressed concrete (PC) continuous girder bridges with corrugated steel webs (CSWs), suitable damping control measures can be used to effectively reduce the seismic response of the bridge. Based on the semi-active control theory, the semi-active control system of a three-span PC continuous girder bridge with CSWs is designed, and the semi-active control system program of the three-span PC continuous girder bridge with CSWs is compiled by MATLAB. The time–history curves of damper energy consumption of active optimal control algorithm and three different semi-active control algorithms are compared and analyzed, as are the time–history curves of main girder displacement, acceleration, and pier internal force with or without semi-active control. The study shows that the rational determination of the weight matrix coefficient can make the active control achieve a better vibration absorption effect and economy. The semi-active control algorithm of Hrovat has the best vibration absorption effect, which is closest to that of the active optimal control algorithm. Under the state of semi-active control, the average vibration absorption rate of displacement and acceleration of the main girder with CSWs are 71% and 20%, respectively. The time–history curve of bending moment and shear force in the pier bottom is similar, and the average vibration absorption rate of bending moment and shear force at the bottom of pier #2 is 70%. At the same time, the average vibration absorption rate of bending moment and shear force at the bottom of pier #3 is between 42% and 48%. The semi-active control measure has a good vibration absorption effect on the overall seismic response of the PC continuous girder bridges with CSWs. This study provides a certain reference for the seismic reduction and isolation design of composite structure bridge with CSWs.